Association between Crowding and the Effective Maxillary and Mandibular Length among Orthodontic Patients of Kathmandu, Nepal. - Gupta, Sanjay Prasad; Dahal , Samarika; Rauniyar , Shristi (Europasian Journal of Medical Sciences, 2021)
Background: During orthodontic consultation, the most frequent major complaint of the patients is dental crowding, which is caused by a disparity between the arch length and tooth size. Objective: The purpose of this study was to evaluate the association between crowding and the effective maxillary and mandibular length in Nepalese orthodontic patients. Methods: The orthodontic records of 390 people (from January 2018 to December 2020) were randomly selected and classified into three skeletal malocclusions based on the ANB angle (Angle formed by point A and point B at the nasion). Subjects with skeletal malocclusions were subdivided into two groups depending on the degree of crowding in the mandibular arch: Group 1 had crowding of < 3mm, and Group 2 had crowding of >3mm. On pretreatment casts, digital vernier calipers (Digimatic, Precise, India) were used to assess dental arch crowding, whereas, on a pretreatment lateral cephalogram, digital cephalometric analysis (Vistadent OC 1.1, USA) was done to quantify effective maxillary and mandibular length. Inter-group comparisons were assessed using a one-way analysis of variance. The correlation was assessed by Pearson’s correlation coefficient (p≤0.05). Results: There was a statistically significant difference in effective maxillary and mandibular length among skeletal malocclusions (p<0.05). Skeletal Class II malocclusion had the greatest mandibular crowding, while skeletal Class III malocclusion had the least. The effective maxillary and mandibular lengths and dental crowding had a significant but weak inverse correlation, whereas a strong but moderate positive correlation existed between the maxillary and mandibular effective lengths (r=0.674) and also between maxillary and mandibular crowding (r=0.631). Conclusion: Effective maxillary length was highest in skeletal class II malocclusion whereas effective mandibular length was highest in skeletal class III malocclusion. The shorter effective maxillary and mandibular lengths showed a weak association with dental crowding. DOI: https://doi.org/10.46405/ejms.v3i2.380